Analysis of serum electrolyte and lipid profile in young Bangladeshi female with Type II Diabetes. Issue 1 (1st January 2018) - Billah, Md. Mustahsan; Rana, S.M. Masud; Akter, Nahida; Hossain, Mohammad Salim
Abstract: Objective : Type 2 Diabetes Mellitus is one of the most serious and common public health problems and metabolic disorder in both developed and developing countries. Diabetic patient may suffer from imbalanced electrolyte and lipid profile due to complications of diabetes mellitus and the medication they receive. Electrolytes and lipids have noteworthy roles, and changes in their concentrations provide significant signs of disease progression in a number of non-communicable diseases like diabetes. As there is a very few study of electrolyte and lipid profile in young Bangladeshi female diabetic patients, we investigated to identify the status of serum electrolytes and lipid profile with fasting blood glucose levels in type 2 diabetic female subjects with age ranging from 20 to 30. Subjects : Thirty-five female type 2 diabetes mellitus patients and 15 non-diabetic healthy control female volunteers of 20–30 age were recruited to determine serum glucose, electrolytes (Na +, K +, Cl −, and HCO3 − ), and lipid profiles (total cholesterol, triglyceride, HDL, and LDL). Result : The mean levels of electrolytes except K + and lipid profile except HDL were found significantly higher ( p  < 0.001) in comparison with control group. While, there was significant ( p  < 0.05) decrease in the serum levels of K + and HDL in all diabetics. Conclusion : These results presented some variations from other research having different age and sex. Therefore, it can be concluded that there might have an effect of age and sex differences on lipid and electrolyte profile. This abnormal biochemical profile could be a noteworthy sign of diabetes associated disease and may have great potential as a diagnostic tool in clinical practice.